Venture deals : be smarter than your lawyer and venture capitalist - Feld, Brad.; Mendelson, Jason, 1971- (Hoboken, N. J. : Wiley, 2011)
'An engaging guide to excelling in today's venture capital arenaBeginning in 2005, Brad Feld and Jason Mendelson, managing directors at Foundry Group, wrote a long series of blog posts describing all the parts of a typical venture capital Term Sheet: a document which outlines key financial and other terms of a proposed investment. Since this time, they've seen the series used as the basis for a number of college courses, and have been thanked by thousands of people who have used the information to gain a better understanding of the venture capital field.Drawn from the past work Feld and Mendelson have written about in their blog and augmented with newer material, Venture Capital Financings puts this discipline in perspective and lays out the strategies that allow entrepreneurs to excel in their start-up companies. Page by page, this book discusses all facets of the venture capital fundraising process. Along the way, Feld and Mendelson touch on everything from how valuations are set to what externalities venture capitalists face that factor into entrepreneurs' businesses. Includes a breakdown analysis of the mechanics of a Term Sheet and the tactics needed to negotiate Details the different stages of the venture capital process, from starting a venture and seeing it through to the later stages Explores the entire venture capital ecosystem including those who invest in venture capitalist Contain standard documents that are used in these transactions Written by two highly regarded experts in the world of venture capital The venture capital arena is a complex and competitive place, but with this book as your guide, you'll discover what it takes to make your way through it'--
Includes index.
Keywords: Venture capital; New business enterprises -- Finance